PENGARUH INTEREST RATEBI, SPREAD OF INTEREST RATE, FLUKTUASI NILAI TUKAR RUPIAH DAN KREDIT BERMASALAH TERHADAP PROFITABILITAS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2011-2015 - UTAMI, EVA WAHYU; NUGRAHANI, CAHAYA (KIAT BISNIS, 2016)
Profitability or ability obtain get the profit is an size measure in presentase used to assess how far company able to yield the profit of at accepted earnings storey;level. Profitability number expressed for example in profit number [of] before Iease, invesment profit, earning per share, and company profit. Assess this profitability become the size measure for health of company and menunjukan of company efficiency. Intention of this research for the mengatahui of what Interest of Rate BI, Spread of Interest Rate, Fluctuation of Exchange Rate of Rupiah and Credit A Period of to Profitability of Banking Company which Enlist In Effect Exchange of Year Indonesia 2011-2015. Population used in this research is banking company enlisted in Effect Exchange of Indonesia in the year 2011-2015 with the population amount 43. Election Sampel by using purposive sampling. Pursuant to sampel, obtained by 20 company becoming sampel in this research. Data analyzer used in this research use the doubled regresi. Result of this research conclude that Interest of Rate BI, spread of of interest of rate and credit of A period of having an effect on to profitability. While Fluctuation of Exchange Rate of Rupiah [do] not berppengaruh to profitability. Keyword : Interest of Rate BI, Spread of Interest Rate, Fluctuation of Exchange Rate Rupiah, Credit of A period